A modernidade vista desde o Sul Global: três contribuições teóricas recentes - Marcos de Jesus Oliveira (Universidade do Vale do Rio dos Sinos (UNISINOS), 2018)
The concept of modernity has been one of the most discussed in the social sciences since its process of institutionalization in Western universities and research centers. However, as Durkheim’s, Marx’s, and Weber’s interpretations, and more contemporaneously, those of Giddens, Touraine, and Habermas, have become hegemonically classical within the social sciences, debates around its limits and scope as well as its problems have been accumulating. Among those debates, the present work intends to present the contributions by Walter Mignolo, Kuan-Hsing Chen e Salman Sayyid, whose thought has set a series of theoretical problems not covered by European theories of modernity. Together, the authors reveal new ways to think a cartography about modernity, i.e., the diagrams of forces involved in its rhetoric.